Repeated adjacent segment diseases and fractures in osteoporotic patients: a case report - Chen HY; Chen CL; Chen WL (Dove Medical Press, 2016)
Hsin-Yao Chen,1 Chiu-Liang Chen,1,2 Wei-Liang Chen3 1Department of Orthopedic Surgery, Changhua Christian Hospital, Changhua City, 2Liberal Arts Center of Da Yeh University, Dacun Township, Changhua County, Taiwan; 3Department of Clinical Image, Changhua Christian Hospital, Changhua City, Changhua County, Taiwan Background: Pedicle screw instrumentation for treating spinal disorder is becoming increasingly widespread. Many studies have advocated its use to facilitate rigid fixation for spine; however, adjacent segmental disease is a known complication. Instrumented fusion for osteoporotic spines remains a significant challenge for spine surgeons. Prophylactic vertebroplasty for adjacent vertebra has been reported to reduce the complications of junctional compression fractures but has raised a new problem of vertebral subluxation. This case report is a rare and an extreme example with many surgical complications caused by repeated instrumented fusion for osteoporotic spine in a single patient. This patient had various complications including adjacent segmental disease, vertebral subluxation, and junctional fractures on radiographs and magnetic resonance images.Case presentation: An 81-year-old Taiwanese woman underwent decompression and instrumented fusion of L4-L5 in Taiwan 10 years ago. Due to degenerative spinal stenosis of L3-L4 and L2-L3, she had decompression with instrumented fusion from L5 to L1 at the previous hospital. However, catastrophic vertebral subluxations with severe neurologic compromise occurred, and she underwent salvage surgeries twice with prolonged instrumented fusion from L5 to T2. The surgeries did not resolve her problems of spinal instability and neurologic complications. Eventually, the patient remained with a Frankel Grade C spinal cord injury.Conclusion: Adjacent segmental disease, junctional fracture, and vertebral subluxation are familiar complications following instrumented spinal fusion surgeries for osteoporotic spines. Neurologic injuries following long instrumentation are often serious and difficult to address with surgery alone. Conservative treatments should always be contemplated as an alternative method for patients with poor bone stock. Keywords: osteoporotic spine, vertebral subluxation, junctional fracture, instrumented fusion, complication